2008
DOI: 10.1016/j.jpcs.2008.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening of nanoscale anatase Ti0.9Zr0.1O2 upon multiple compression cycles

Abstract: The compression behavior of nanoscale Zr-doped anatase was studied by means of a diamond anvil cell experiment with alternating cycles of compression and decompression in the stability field of anatase (up to 13 GPa). We found that multiple cycles of compression lead to stiffening of the material: Precompressed samples of nanoanatase Ti 0.9 Zr 0.1 O 2 have a higher bulk modulus (K 0 = 249(9) and 266(6) GPa) compared to the sample when compressed for the first time (K 0 = 211(7) GPa). Upon compression, the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…5c at P 4 8 GPa as belonging to a disordered nc anatase Ti 0.9 Zr 0.1 O 2 . 21,23 The hysteretic compression-decompression paths (Fig. 5c) and smaller V o of the decompressed 12 AE 3 nm Ti 0.9 Zr 0.1 O 2 anatase (Table 3) suggest partial structural disorder and densification acquired within the non-elastic regime.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…5c at P 4 8 GPa as belonging to a disordered nc anatase Ti 0.9 Zr 0.1 O 2 . 21,23 The hysteretic compression-decompression paths (Fig. 5c) and smaller V o of the decompressed 12 AE 3 nm Ti 0.9 Zr 0.1 O 2 anatase (Table 3) suggest partial structural disorder and densification acquired within the non-elastic regime.…”
Section: Resultsmentioning
confidence: 98%
“…It is suggested that the inclusion of P-V data belonging to both ordered and disordered Ti 0.9 Zr 0.1 O 2 anatase in the Birch-Murnaghan equation fit potentially led to the anomalous EoS parameters in the earlier work. 22,23 The larger K o value obtained for the precompressed 15 nm Ti 0.9 Zr 0.1 O 2 anatase (Table 3) indicates contributions from both nanocrystallinity and ''frozen-in'' (not fully reversible) disorder.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The has also been much interest in the properties of nano structures of TiO 2 and notably when such structures are subject to extreme conditions of temperature or pressure [1, [3][4][5][6][7][8][9]. There is particle size behavior under pressure as compared to the bulk counterpart and often changes in compressibility as measured by a bulk modulus [8,9] are reported.…”
Section: Introductionmentioning
confidence: 99%